The effectiveness of nurse-led antenatal education on maternal self-efficacy: an evidence-based approach - Huda Hamdy Mohammed; Azza Ali Abd El Hamed; Nagwa Abd El- Fadil Afefy; Nadine Alaa Sherif; Sahar Mansour Ibrahim (BMC Nursing)
Abstract Background Improving maternal self-efficacy during childbirth is a key objective of antenatal care, with evidence suggesting that nurse-led education can play a critical role in this process. However, the overall effectiveness and consistency of these interventions across delivery formats remain unclear. Objective To provide an evidence-based analysis of the effectiveness of nurse-led antenatal education programs on maternal childbirth self-efficacy using quantitative synthesis and subgroup comparisons. Methods A comprehensive search was conducted across six databases (PubMed, CINAHL, Scopus, Web of Science, PsycINFO, and Embase) to identify relevant studies published from January 2000 to April 2025. Twenty studies (randomized controlled trials and quasi-experimental designs) were included. A meta-analysis was conducted to estimate the pooled effect size, assess heterogeneity, and evaluate subgroup differences by delivery format (face-to-face, digital, hybrid). Risk of bias was assessed using the ROB 2 tool, and publication bias was evaluated using funnel plot symmetry, Egger’s test, and Rosenthal’s fail-safe N. The protocol was registered with PROSPERO (CRD420251058392). Results The pooled standardized mean difference (SMD) indicated a significant moderate-to-large effect of nurse-led antenatal education on maternal self-efficacy (SMD = 0.73; 95% CI: 0.69–0.77). Subgroup analysis showed the strongest and most consistent effects for face-to-face programs, while digital interventions demonstrated comparable efficacy with greater variability. Hybrid models yielded moderate but reliable outcomes. Publication bias was not detected, and heterogeneity was moderate (I² < 60%). All included studies reported positive effects. Conclusion This evidence-based analysis confirms that nurse-led antenatal education substantially improves maternal self-efficacy across various delivery models. These findings support the integration of nurse-led programs into routine prenatal care, with the potential for digital and hybrid formats to enhance scalability and access. Future research should focus on standardizing outcome measures and evaluating long-term impacts.